Relative importance of climate and mountain pine beetle outbreaks on the occurrence of large wildfires in the western USA - Mietkiewicz, Nathan; Kulakowski, Dominik (Ecological applications, 2016)
Extensive outbreaks of bark beetles have killed trees across millions of hectares of forests and woodlands in western North America. These outbreaks have led to spirited scientific, public, and policy debates about consequential increases in fire risk, especially in the wildland-urban interface (WUI), where homes and communities are at particular risk from wildfires. At the same time, large wildfires have become more frequent across this region. Widespread expectations that outbreaks increase extent, severity, and/or frequency of wildfires are based partly on visible and dramatic changes in foliar moisture content and other fuel properties following outbreaks, as well as associated modeling projections. A competing explanation is that increasing wildfires are driven primarily by climatic extremes, which are becoming more common with climate change. However, the relative importance of bark beetle outbreaks vs. climate on fire occurrence has not been empirically examined across very large areas and remains poorly understood. The most extensive outbreaks of tree-killing insects across the western United States have been of mountain pine beetle (MPB; Dendroctonus ponderosae), which have killed trees over > 650,000 km², mostly in forests dominated by lodgepole pine (Pinus contorta). We show that outbreaks of MPB in lodgepole pine forests of the western United States have been less important than climatic variability for the occurrence of large fires over the past 29 years. In lodgepole pine forests in general, as well as those in the WUI, occurrence of large fires was determined primarily by current and antecedent high temperatures and low precipitation but was unaffected by preceding outbreaks. Trends of increasing co-occurrence of wildfires and outbreaks are due to a common climatic driver rather than interactions between these disturbances. Reducing wildfire risk hinges on addressing the underlying climatic drivers rather than treating beetle-affected forests.